Sex-specific dispersal behaviour of crawlers in the mealybug Planococcus citri - Ross, L.; Pen, I.; Shuker, D.M. (ENTOMOLOGIA HELLENICA, 2011)
Sex-specific dispersal can have important evolutionary and ecological implications, influencing local population structure and sex ratio, as well as the speed at which new habitats can be colonized. In scale insects, first-instar nymphs (crawlers) are assumed to be the main dispersal stage. Although all scale insects are extremely sexually dimorphic, in most species the sexes are indistinguishable as crawlers. Here we consider the mealybug Planococcus citri (Risso), and dispersal by crawlers to or from resource patches. The aim of this study was to test if: (1) crawler dispersal behaviour differs between the sexes and how this is affected by local conditions (population density and sex ratio); and (2) there is a difference between the sexes in crawler dispersal success to a new host plant. Using two experiments, which differed in how resources were spread between dispersal sources and sinks, we show that male and female nymphs do not differ in their dispersal behaviour or in their dispersal success when dispersal is via crawler locomotion. These laboratory experiments are an important starting point for understanding the evolution of dispersal behaviour of P. citri in the field, suggesting that more attention might need to be paid to different methods of dispersal as well as crawler locomotion.